Hannes Leidinger et al., Habsburgs schmutziger Krieg - Lompar, Rastko (Balcanica - Annual of the Institute for Balkan Studies, 2023)
Hannes Leidinger, Verena Moritz, Karin Moser and Wolfram Dornik, Habsburgs schmutziger Krieg. Vienna: Residenz Verlag, 2014, 328 p.